Paradox of Criminal Provisions Formulation Regarding Reporting of Political Party Campaign Funds in the 2024 General Election - ., Syamsuddin; ., Hartiwiningsih; Rustamaji, Muhammad (Journal of Ecohumanism, 2024)
Political parties as a form of organization whose scope is the political field make it a primary position in modern democracy which is required to be in line with democratic norms and election principles. The characteristics of political parties as legal subjects (subjectum juris) of corporations/public legal entities that can also act in the private sphere that are attached to legal consequences for all actions or deeds, and legal relationships, both in the administrative, civil, and criminal spheres. One of the actions or legal acts of political parties in the Election is the legal obligation to report campaign funds honestly, accountably, and transparently in accordance with the principles of organizing elections as a legal act that has the potential to have administrative and criminal consequences. In several formulations of criminal provisions of the Election Law which are specifically formulated for political parties as legal subjects (subjectum juris) of corporations, although the construction of the articles does not explicitly mention political parties, but refers to the phrase Election Participants which consists of 5 Articles, namely Article 496, Article 525 Paragraph (2), Article 526 Paragraph (2), Article 527, and Article 528 Paragraph (1) of the a quo Law. One of the actions or legal acts of political parties that has the potential to be subject to criminal penalties is the provision of Article 496 of the a quo Law related to election participants who intentionally provide false information in the Election campaign fund report, which constructively-holistically reaps problems in the actions or legal actions of political parties as election participants as well as the problem of deadlocked norms in related articles in the a quo Law.